MA’ÂYIR AL-ADAWÂT AL-TAQWÎMIYAH LI AL-KITÂB AL-MADRASÎ LI AL-LUGHAH AL-‘ARABIYAH LI AL-INDÛNÎSIYÎN : DIRÂSAH BINÂIYAH TAKÂMULIYAH - Pransiska, Toni; Widodo, Sembodo Ardi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
There are several problems regarding textbooks in Indonesia, especially Arabic textbooks. First, the procurement stage, such as the process of writing, obtaining texts, evaluating, and publishing. Second, the distribution stage such as access to textbooks, and purchasing power of textbooks. Third, the stage of the use of books which covers the confusion of teachers in using textbooks and the period of use of school books. The aspects of the evaluation of textbooks will be important in the future. Therefore, this research aims to construct instrumental assessment of arabic teaching books from national and international perspectives. This is important to do as an effort to obtain quality Arabic textbooks with international insight. This research uses a Research and Development (R & D) approach and content analysis. The results of this study show that the Arabic textbook assessment instrument made by the National Education Standards Agency (BSNP) and the American Council on Teaching of Foreign Languages (ACTFL) is still lacking because it does not accommodate all the points and basic elements contained in a Arabic textbooks as a Foreign language. So, the construction of a comprehensive integrated integrative Arabic textbook assessment instrument is absolutely necessary in order to obtain good and quality Arabic textbooks.